Исследование свойств наноструктурного адсорбента - Мартемьянова И. В. Ирина Владимировна; Мосолков А. Ю. Алексей Юрьевич; Плотников Е. В. Евгений Владимирович; Воронова О. А. Олеся Александровна; Журавков С. П. Сергей Петрович; Мартемьянов Д. В. Дмитрий Владимирович; Короткова Е. И. Елена Ивановна (2015, 2015)
Заглавие с экрана